The Effect Of Combination Of Technology Of Planting And Control Of Weeds On The Dominant Value Of Weeds And Rice Productivity - Yuriko Kasim (Universitas Negeri Manado, 2022)
The problem currently arises in lowland rice cultivation is the presence of nuisance plants, namely weeds which can reduce crop yields by up to 90%. Therefore, it is necessary to find a way out by testing several weed control technologies that farmers can use. The objectives of the study were (1) to determine the effect of technology for planting methods, namely Tabela in arrays, evenly spaced tables, and evenly distributed tables, on the growth and production of lowland rice, (2) To determine the effect of weed control technology using herbicides with active ingredients metsulfuron-methyl and 2,4 -D on the growth and production of lowland rice and (3) To determine the effect of the Combination of planting technology and weed control technology on the growth and production of lowland rice. The experiment was carried out using a Randomized Block Design (RAK) as the environmental design. The treatment design was a split-plot design: Main Plot, Planting Method Technology (T): T1 = Array Tables, T2 = Distance Tables, T3 = Tables Spread Evenly. Sub-plots, Weed Control Technology (G): G1 = Herbicide with active ingredient mtsulfuron methyl, G2 = Herbicide with active ingredient 2,4-D, G3 = Combination of mtsulfuron methyl and 2,4-D. Thus there were nine treatments, each treatment was repeated three times, so there were 27 experimental units. One experimental plot measuring 4 x 6 m. The placement of all treatments in the experimental plot was done randomly. The dominant weed species observed were Paspalum disticum, Fibristylis litoralis, Marsilea crenata, Cyperus iria and Echinochloa colonum. The dominant weed species in all treatment combinations observed at 21 DAP were Paspalum distichum, Echinochloa crusgalli, Marsilea crenata, Lersia hexandra and Fimbristylis litoralis. There was no difference in rice production in all treatment combinations. The difference in production only occurred in the average planting method, where the highest production occurred in the T1 treatment.